Healthcare costs of paternal depression in the postnatal period. - Edoka, I; Petrou, S; Ramchandani, P (2011)
BACKGROUND: There is growing evidence that fathers experience depressive symptoms following the birth of a child. The aim of this study was to estimate the healthcare costs of paternal postnatal depression, thereby informing research into cost-effective preventative and treatment interventions for the condition. METHODS: Data on healthcare resource-use over the first 12 months postpartum was collected from 192 fathers recruited from two postnatal wards in southern England. Three groups of fathers were identified: fathers with depression (n=31), fathers at high risk of developing depression (n=67) and fathers without depression (n=94). RESULTS: Mean father-child dyad costs were estimated at £ 1103.51, £ 1075.06 and £ 945.03 (£ sterling, 2008 prices) in these three groups, respectively (P=0.796). After controlling for potentially confounding factors, paternal depression was associated with significantly higher community care costs. CONCLUSION: This study provides useful preliminary insights into the healthcare costs associated with paternal depression during the postnatal period. LIMITATION: The small sample size may, in part, account for the failure to detect statistically significant differences in mean costs between study groups for most cost categories.